2019
DOI: 10.1002/jmri.26882
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement of PI‐RADS v. 2 lexicon among radiologists with different levels of experience

Abstract: Background Evaluation of interobserver agreement of the PI‐RADS v2 lexicon is important to validate the uniformity of this widely used classification. Purpose To determine the interobserver agreement of PI‐RADS v2 lexicon among eight radiologists with varying levels of experience. Study Type Retrospective. Population In all, 160 consecutively imaged men with confirmatory targeted biopsy. Field Strength/Sequence 3T scanner without an endorectal coil. T2‐weighted imaging (T2w), diffusion‐weighted imaging (DWI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
4
23
2
1
Order By: Relevance
“…7 All MRI scans were performed at 3.0 T with axial T1-weighted images (T1WI), multiplane (Axial, coronal, and sagittal) T2-weighted images (T2WI), and axial diffusion weighted imaging (DWI) (measured b-values of 0.400 and 800 seconds/mm 2 , calculated b-value of 2000 seconds/mm 2 ), but without dynamic contrast enhancement (DCE). 8 The prostate nodules found by bpMRI were evaluated by PI-RADS V2 scores by the deputy chief or senior physicians. 9 The lesions were located in detail before the puncture (lesions' position, diameter, distance from the bladder neck, and distance from the dorsal margin of the prostate).…”
Section: Mri Protocolmentioning
confidence: 99%
“…7 All MRI scans were performed at 3.0 T with axial T1-weighted images (T1WI), multiplane (Axial, coronal, and sagittal) T2-weighted images (T2WI), and axial diffusion weighted imaging (DWI) (measured b-values of 0.400 and 800 seconds/mm 2 , calculated b-value of 2000 seconds/mm 2 ), but without dynamic contrast enhancement (DCE). 8 The prostate nodules found by bpMRI were evaluated by PI-RADS V2 scores by the deputy chief or senior physicians. 9 The lesions were located in detail before the puncture (lesions' position, diameter, distance from the bladder neck, and distance from the dorsal margin of the prostate).…”
Section: Mri Protocolmentioning
confidence: 99%
“…Nevertheless, the results of Mussi et al support other studies that have shown improved intrareader agreement and interreader agreement for PI‐RADSv2 scoring with increasing radiologist experience . When assessing individual imaging features, Mussi et al showed the best agreement for observation size, focality, and signal intensity on DWI in the PZ and observation size, signal intensity on DWI, and encapsulated nature in the TZ similar to Rosenkrantz et al…”
mentioning
confidence: 85%
“…In this issue of The Journal of Magnetic Resonance Imaging, Mussi et al sought to answer this question by comparing interobserver agreement levels across a group of eight radiologists with varying experience in prostate MRI when applying PI-RADSv2. 4 The authors of the present study used a very similar methodology to Rosenkrantz et al, 3 namely, radiologists evaluated PI-RADSv2 scoring and individual imaging features in a preselected population of 160 men encompassing a representative number of PZ and TZ observations (130:30 split). Radiologists were provided with the location of observations that had histopathology verified by targeted fusion biopsy.…”
mentioning
confidence: 99%
“…The main target is to build acceptable technical standards for prostate mp-MRI, which makes it clear and simpler with subsequent standardized reporting terms, as well as help the procedure of MRI-guided biopsy. It also develops assessment groups that summarize ranks of the risk that could be helpful to choose and prepare patients for the next steps in management and finally enhance interdisciplinary communications with physicians [6,[9][10][11][12][13][14][15][16][17][18][19]. Having both targeted and systematic biopsy could offer the peak discovery of clinically significant prostate cancer [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous MRI-guided sampling procedures will enhance the recognition of clinically significant PCa as well as decrease the discovery of insignificant cancer decreasing the unnecessary costly treatments and their possible complications [27]. Many studies discussed the interobserver agreement of PI-RADS-v2 in the assessment and discovery of prostate cancer [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The uniqueness of our study is the assessment of interobserver in the peripheral zone (PZ) and the central zone (CZ) separately, as well as the interobserver agreement of the different pulse sequences of PI-RADS-v2.…”
Section: Introductionmentioning
confidence: 99%